Changes in the allocation policy for deceased donor livers in Korea: perspectives from anesthesiologists - Seung Yeon Yoo; Gaab Soo Kim (Anesthesia and Pain Medicine, 2021)
Background The allocation policy for deceased donor livers in Korea was changed in June 2016 from Child-Turcotte-Pugh (CTP) scoring system-based to Model for End-stage Liver Disease (MELD) scoring system-based. Thus, it is necessary to review the effect of allocation policy changes on anesthetic management. Methods Medical records of deceased donor liver transplantation (DDLT) from December 2014 to May 2017 were reviewed. We compared the perioperative parameters before and after the change in allocation policy. Results Thirty-seven patients underwent DDLT from December 2014 to May 2016 (CTP group), and 42 patients underwent DDLT from June 2016 to May 2017 (MELD group). The MELD score was significantly higher in the MELD group than in the CTP group (36.5 ± 4.6 vs. 26.5 ± 9.4, P < 0.001). The incidence of hepatorenal syndrome was higher in the MELD group than in the CTP group (26 vs. 7, P < 0.001). Packed red blood cell transfusion occurred more frequently in the MELD group than in the CTP group (5.0 ± 3.6 units vs. 3.4 ± 2.2 units, P = 0.025). However, intraoperative bleeding, vasopressor support, and postoperative outcomes were not different between the two groups. Conclusions Even though the patient’s objective condition deteriorated, perioperative parameters did not change significantly.